The wine wars the Mondavi affair, globalization and "terroir" - Torrès, Olivier (Palgrave Macmillan, 2006)
"The Mondavi affair illustrates the importance of culture, history, geography and economic and political systems in conditioning our spirit of enterprise and the way in which we do business. It opens up perspectives for reflection in fields as varied as international management and entrepreneurship, local development and political science."--BOOK JACKET